Optimization of PCR Amplification and Sequence Alignment of Pholas orientalis Internal Transcribed Spacers (ITS) for Possible Determination of Origin-Specific Restriction Fragment Lenght Polymorphisms (RFLPs) - Girasol, Mark John G.
Six PCR amplification protocols of the internal transcribed spacers (ITS) for bivalves, which utilized the primers designed by Heath, et al. (1995), were evaluated in this study. However, only that of Breusing (2012) yielded desired brands. This protocol was modified for specificity with Pholas orientalis. The optimized protocol was carried out in a 20-μl reaction containing 1mM gDNA, 0.25μM forward and reverses primers, 0.125U/μl Taq DNA polymerase, 200μM dNTPs, 5mM MgCl2, and 1X Buffer A. The optimized cycling conditions include an initial denaturation of 94°C for 5 min, followed by 30 cycles of denaturation at 94°C for 30 s, annealing at 55.5°C for 1 min, and extension at 72°C for 1 min 45 s, and a final extension of 72°C for 7 min. Extension time was varied from 45 s, 1 min, 1 min 30 s, to 1 min 45 s, however, optimum band intensity was achieved at extension time of 1 min 45 s. Utilizing ImageLab software, band size measured 789bp. RFLP assay employed four restriction enzymes: BamHI, BstDEI, VspI, and BstV2I. Only BstDEI was able to digest the amplicons into two fragments (485bp and 316bp), however, it was not able to show fragment polymorphisms in DNA samples coming from different sites. This was confirmed by sequence alignment with four Perna species. BstDEI restriction site resides in the 5.8S rDNA, which is a highly conserved region in the ITS. Therefore, BstDEI is not helpful in determining origin-specific RFLPs.